Enthalpies Of Dissociation Of Pure Methane And Carbon Dioxide Gas Hydrate - Nasir, Qazi; K. K. Lau; Lal, Bhajan (Zenodo, 2014)
In this study the enthalpies of dissociation for pure methane and pure carbon dioxide was calculated using a hydrate equilibrium data obtained in this study. The enthalpy of dissociation was determined using Clausius-Clapeyron equation. The results were compared with the values reported in literature obtained using various techniques. : {"references": ["E.G. Hammerschmidt, \"Formation of Gas Hydrates in Natural Gas\nTransmission Lines\",Ind. Eng. Chem, vol. 26, pp.851-855, 1934", "B. Tohidi, , R. W. Burgass, A. Danesh, K. K. Ostergaard, A. C. Todd,\n\"Improving the accuracy of gas hydrate dissociation point\nmeasurement\", Ann. N. Y. Acad. Sci, vol. 919, pp. 924 \u2013 931, 2000", "P. Skovborg, P. Rasmussen, 'Comments on: hydrate dissociation\nenthalpy and guest size\", Fluid Phase Equilib,vol. 96, pp. 223-231 1994", "A. Hachikubo, A. Miyamoto, K. Hyakutake, K. Abe, H. Shoji, \"Phase\nequilibrium studies on gas hydrates formed from various guest\nmolecules and powder ice\", The fourth International conference on gas\nhydrates, Yokohama, Japan, 2002", "T. Nakamura, T. Makino, T. Sugahara, K. Ohgaki, \"Stability boundaries\nof gas hydrates helped by methane-structure-H hydrates of\nmethylcyclohexane and cis-1,2-dimethylcyclohexane\", Chem. Eng.Sci,\nvol. 58, pp. 269-273, 2003", "M. Kharrat, D. Dalmazzone, \"Experimental determination of stability\nconditions of methane hydrate in aqueous calcium chloride solutions\nusing high pressure differential scanning calorimetry\", J. Chem.\nThermodyn, vol. 35, pp. 1498-1505, 2003", "A. H. Mohammadi, R. Anderson, B. Tohidi, \"Carbon monoxide\nclathrate hydrates: Experimental equilibrium data and thermodynamic\nmodeling\", ALChE. J, vol. 51, pp. 2825-2833, 2005", "D. B. Robinson, B. R. Mehta, \"Hydrates in the propane-carbon dioxidewater\nsystem\", J.Can. Petro, vol. 10, pp. 33-35, 1971", "K. M. Sabil, G.J. Witkampa, C.J. Peters, \"Estimation of enthalpies of\ndissociation of simple and mixed carbon dioxide hydrates from phase\nequilibrium data\", Fluid Phase Equilib, vol. 290, pp. 109-114, 2010\n[10] G. Soave, \"Equilibrium Constants from a Modified Redlich\u2013Kwong\nEquation of State\", Chem. Eng. Sci, vol. 27, pp. 1197-1203, 1972\n[11] J.H. Yoon, Y. Yamamoto, T. Komai, H. Haneda, Rigorous \"Approach to\nthe Prediction of Heat of Dissociation of Gas Hydrates\", Ind. Eng.\nChem. Res, vol. 42, pp. 1111-1114, 2003\n[12] G.K. Anderson, \"Enthalpy of dissociation and hydration number of\ncarbon dioxide hydrate from Clapeyron equation\", J. Chem. Thermodyn,\nvol. 35, pp.1171-1183, 2003\n[13] V.A. Kamath, 'A Study of Heat Transfer Characteristics during\nDissociation of Gas Hydrates\", in, University of Pittsburgh, 1984.\n[14] S.-P. Kang, H. Lee, B.-J Ryu, \"Enthalpies of dissociation of clathrate\nhydrate of carbon dioxide,nitrogen, (carbon dioxide+ nitrogen), and\ncarbon dioxide + nitrogen + tetrahydrofuran)\",J. Chem. Thermodyn, vol.\n33, pp. 513-521,200.\n[15] T. Uchida, A. Takagi, J. Kawabata, S. Mae, T. Hondoh, \"Raman\nspectroscopic analyses of the growth process of CO2 hydrates\", Energy\nConvers. Manage.Vol. 36, pp. 547\u2013550, 1995\n[16] Y.P. Handa, Compositions, \"Enthalpies of dissociation, and Heat\ncapacities in the range 85 to 270K for clathrate hydrate of CH4 , C2H6,\nC3H8\", J.Chem.Thermo, vol. 18, pp 15, 1986a\n[17] R.M. Rueff, E.D. Sloan, \"Y.V. F, Heat capacity and Heat of dissociation\nof methane hydrates\", AlChE Journal, vol. 34, pp. 1468, 1988\n[18] J.S. Lievois, R. Perkins, R.J. Martin, R. Kobayashi, \"Development of an\nautomated, High pressure heat flux calorimeter and its application to\nmeasure the heat of dissociation and hydrate number of methane\nhydrate\", Fluid Phase Equilib, vol. 59, pp.73, 1990\n[19] J.P. Long, \"Gas Hydrate Formation Mechanisim and Kinetic Inhibition\",\nin, Colorado School of Mines, 1994.\n[20] A. Delahaye, L. Fournaison, S. Marinhas, I. Chatti, J.-P Petitet, D.\nDalmazzone, W. F\u02dcurst, \"Effect of THF on Equilibrium Pressure and\nDissociation Enthalpy of CO2 Hydrate Applied to Secondary\nRefrigeration\", Ind. Eng. Chem.Res, vol. 45, pp.391-397, 2006."]}